Hypo-CpG methylation controls PTEN expression and cell apoptosis in irradiated lung. (2nd August 2016) - Zhang, Xiuwu; Hadley, Caroline; Jackson, Isabel L.; Zhang, Yi; Zhang, Angel; Spasojevic, Ivan; Haberle, Ines Batinic; Vujaskovic, Zeljko
Abstract: Purpose: The current study was designed to address our hypothesis that oxidative stress secondary to the ionizing event upregulates phosphatase and tensin homolog (PTEN) mRNA and protein in the lungs of C57BL/6J mice through oxidative DNA damage resulting in CpG hypomethylation in the PTEN promoter. Methods: Fibrosis-prone C57BL/6J mice were exposed to 0 or 15 Gy of 320 kVp X-rays to the whole thorax. Lung tissue was serially harvested at time points between one day and six months postirradiation. Tissue levels of PTEN mRNA, total protein, and phosphorylated PTEN, as well as CpG methylation of the PTEN promoter, expression of DNA methyltransferases 1 (Dnmt1) and 3a (Dnmt3a), NADPH oxidase 4 (Nox4) protein expression, and DNA damage levels were measured. The induction of DNA damage and global methylation changes were also examined in hydrogen peroxide (H2 O2 )-treated human umbilical vein endothelial cells (HUVECs) and human bronchial epithelial cells in vitro . Results: These experiments demonstrate that PTEN mRNA and protein, Nox4 protein, and DNA damage levels increase continuously from one day to six months following radiation exposure. Elevated PTEN transcription and translation are likely the result of the observed decrease in CpG methylation of the PTEN promoter region. This finding is not consistent with the observed increase in Dnmt1 and Dnmt3a protein expression, implicating an alternative mechanism as the driving force behind hypomethylation. In vitro results provide evidence that H2 O2 can induce DNA damage and affect DNA methylation status. The Mn porphyrin-based superoxide dismutase (SOD) mimic MnTnHEx-2-PyP 5+  exhibited partial rescue from radiation-induced hypomethylation. Conclusions: Taken together, these data suggest that reactive oxygen species (ROS)-induced DNA damage results in hypomethylation of the PTEN promoter, upregulation of PTEN mRNA and protein, and a subsequent increase in apoptosis in irradiated lung tissue.